2008
DOI: 10.1109/tap.2008.927573
|View full text |Cite
|
Sign up to set email alerts
|

Equiangular Spiral Antenna Backed by a Shallow Cavity With Absorbing Strips

Abstract: Abstract-When a conducting shallow cavity is placed behind an equiangular spiral to obtain a unidirectional beam, the inherent wideband characteristics of the spiral deteriorate. To restore the wideband characteristics, a ring-shaped absorbing strip (R-ABS) is placed under the spiral arms. Analysis of the equiangular spiral with the R-ABS is performed using the finitedifference time-domain method. It is found that the R-ABS successfully restores the wideband characteristics. Subsequently, the R-ABS is divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Figure 16 shows that the metal around the antenna sharply reduces the return loss. Reference [30] indicated that the absorbing material can improve the return loss. However, the efficiency and gain of the antenna are reduced at the same time.…”
Section: Design Of the Metallic Shell Of The Antipodal Vivaldimentioning
confidence: 99%
“…Figure 16 shows that the metal around the antenna sharply reduces the return loss. Reference [30] indicated that the absorbing material can improve the return loss. However, the efficiency and gain of the antenna are reduced at the same time.…”
Section: Design Of the Metallic Shell Of The Antipodal Vivaldimentioning
confidence: 99%
“…To eliminate backside radiation, planar spirals are generally backed by an absorber filled cavity [5]- [8] which leads to a loss in the gain. Another approach is to place a Perfect Electric Conductor plate (PEC) behind the antenna, at a quarter wavelength distance, for a specified frequency.…”
Section: Design Of Boresight Reference Antenna and Planar Printedmentioning
confidence: 99%
“…Generally, there are two methods to realize it. One way is to add electromagnetic absorber in the backside cavity of antenna [3,4]. However, this will reduce the efficiency of the antenna, and there is a tradeoff among the cavity thickness, bandwidth, and the antenna gain.…”
Section: Introductionmentioning
confidence: 99%